Humoral response to EBV is associated with cortical atrophy and lesion burden in patients with MS. Issue 1 (February 2016) - Zivadinov, Robert; Cerza, Nicole; Hagemeier, Jesper; Carl, Ellen; Badgett, Darlene; Ramasamy, Deepa P.; Weinstock-Guttman, Bianca; Ramanathan, Murali
Abstract : Objective: Because dysregulated Epstein-Barr virus (EBV)-infected B cells may induce meningeal inflammation, which contributes to cortical pathology in multiple sclerosis (MS), we investigated associations between antibody responses to EBV and development of cortical pathology in MS. Methods: We included 539 patients with MS (369 with relapsing-remitting MS, 135 with secondary progressive MS, and 35 with primary progressive MS), 66 patients with clinically isolated syndrome (CIS), 63 patients with other neurologic diseases (OND), and 178 age- and sex-matched healthy controls (HC). All participants were scanned on 3T MRI. Serum samples were analyzed for IgG antibodies against EBV viral capsid antigen (VCA) and EBV nuclear antigen-1 (EBNA-1), and their quartiles were determined on the whole study sample. Differences between the study groups were assessed using analysis of covariance adjusted for multiple comparisons. Results: More than 30% of patients with MS and CIS presented with the highest quartile of anti-EBV-VCA and -EBNA-1 status compared to ⩽10% of HC ( p < 0.001). The figures were 9 (14.3%) and 7 (12.3%) for patients with OND. Patients with MS with the highest quartile of anti-EBV-VCA showed significantly increased T2 lesion volume ( p = 0.001), T1 lesion number ( p = 0.002), and T1 lesion volume ( p = 0.04) and decreased gray matter ( p = 0.041) and cortical ( p = 0.043) volumes compared to patients with MS with lower quartiles. No significant differences of MRI outcomes in patients with CIS, patients with OND, and HC with lower or highest quartiles of anti-EBV-VCA and -EBNA-1 were detected. Conclusions: Humoral response to anti-EBV-VCA and -EBNA-1 is associated with more advanced cortical atrophy, accumulation of chronic T1 black holes, and focal white matter lesions in patients with MS.